Exploring Compensations for Demographic Disadvantage in Science Talent Development. Issue 168 (7th November 2019) - Subotnik, Rena F.; Stoeger, Heidrun; Luo, Linlin
Abstract: This study explores factors enhancing the likelihood that three demographically disadvantaged groups of selective science high school graduates would complete a university STEM degree 4–6 years later. The target groups are labeled as disadvantaged in terms of STEM pipeline persistence compared to school peers, and include: (1) women, (2) those without a parent in a STEM field, and (3) those whose parents were not educated beyond high school. Employing Social Cognitive Career Theory as a conceptual framework, we focus on two categories of factors. Individual factors incorporate motivation and career intention brought to the high school experience. Environmental factors include graduates' high school experiences related to their STEM interest and capacity development. The individual variables include: STEM career intentions prior to high school, motivation for attending a specialized science high school, and motivation for pursuing advanced science courses in high school. Environmental factors include whether participants partook in an authentic research experience, had a mentor, felt they belonged at the school, maintained their interest in STEM as well as perceived intellectual capacity for STEM throughout high school. The results have promising implications for educational policy associated with STEM talented students.